Peningkatan Kemampuan Membaca Huruf Melalui Penerapan Media Puzzle di RA Nurul Islam Paron Ngawi - Walida, Ziyana (JECED : Journal of Early Childhood Education and Development, 2023)
This study aims to improve early childhood letter reading skills through Puzzle media at RA Nurul Islam Paron Ngawi. Using the Classroom Action Research (PTK) method, this research consists of three cycles, each of which includes planning, action, observation, and reflection. The research subjects were six children in group A, consisting of three boys and three girls. Data were collected through observation, interviews with teachers and parents, and documentation. The results showed that the application of Puzzle media significantly improved children’s letter reading ability. In the first cycle, only 16.6% of children reached the minimum completion criteria (KKM). This percentage increased to 49.8% in the second cycle, and 83% in the third cycle. This increase shows the effectiveness of Puzzle media in helping children recognize letters better and making the learning process more interactive and fun. The research also underlines the importance of the teacher’s role in optimizing the use of learning media. With reflection and improvements made in each cycle, teachers managed to improve the quality of learning and overcome obstacles faced, such as children’s lack of patience in reading letters.